1992
DOI: 10.1021/bi00152a039
|View full text |Cite
|
Sign up to set email alerts
|

Substrate stereospecificity of phosphatidylinositol-specific phospholipase C from Bacillus cereus examined using the resolved enantiomers of synthetic myo-inositol 1-(4-nitrophenyl phosphate)

Abstract: The substrate stereospecificity of phosphatidylinositol-specific phospholipase C from Bacillus cereus is examined using the resolved optical isomers of synthetic myo-inositol 1-(4-nitrophenyl phosphate), a chromogenic substrate for the phospholipase. The synthetic route employs mild acid-labile protecting groups and separation of the substituted myo-inositol enantiomers as the (-)-camphanyl ester diastereomers. Measurements of the initial rates of cleavage of the D and L enantiomers of the nitrophenyl substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Above all, 4-nitrophenyl 1-phosphoinositol was synthesized and applied to PI-PLC assay (Leigh et al, 1992). In this assay, the enzyme activity is easily measured by p-nitrophenol formation (Fig.…”
Section: Methods Of Pi-plc Assay and Acquisition Of Highly Purifmentioning
confidence: 99%
See 1 more Smart Citation
“…Above all, 4-nitrophenyl 1-phosphoinositol was synthesized and applied to PI-PLC assay (Leigh et al, 1992). In this assay, the enzyme activity is easily measured by p-nitrophenol formation (Fig.…”
Section: Methods Of Pi-plc Assay and Acquisition Of Highly Purifmentioning
confidence: 99%
“…In some cases, however, the samples must be further applied to Phenyl Sepharose column chromatography (Griffith et al, 1991) Figure 6. The reactions in the bacterial PI-PLC assays using (a) 4-nitrophenyl 1-phosphoinositol (Leigh et al, 1992) and (b) pyrene PI (Hendrickson, 1999;Hendrickson et al, 1992) as the substrates.…”
Section: Methods Of Pi-plc Assay and Acquisition Of Highly Purifmentioning
confidence: 99%
“…, 1991a, b). Synthesis of the chromogenic racemic PI analogue DPG-PI utilises simple protection and deprotection strategies (Campbell, 1992;Campbell and Fraser-Ried, 1994); the racemic analoque being adequate for present purposes, since it has been reported that nonsubstrate PI isomers are not PI-PLC inhibitors (Leigh et al, 1992). Employing a continuous "P NMR assay, allowing monitoring and identification of reactants and products, kinetic analysis demonstrated the turnover rate of DPG-PI to be 8% of that of natural PI, in the presence of Triton X-100 and HEPES buffer.…”
Section: Hplc Assay: Pi-plc Metallomicelle Modelmentioning
confidence: 99%
“…Although PI-PLC isozymes do not display strict requirements regarding the structure of the leaving group, [2,8] high hydrophobicity is required for both tight binding and high activity. [17] For example, p-nitrophenyl inositol phosphate (PNPIP) does not display saturation-kinetics behavior (in the practical range of concentration), [18] and is a slightly less efficient substrate than PI (in terms of k cat ) [10] despite the fact that the pK a value of its PNP leaving group is seven orders of magnitude lower than that of DAG. Clearly, the cleavage of PNPIP and other nonhydrophobic chromogenic substrates by PLC lacks some important catalytic elements; therefore such substrates are not suitable for studies of the mechanistic aspects of PI-PLC reactions.…”
mentioning
confidence: 99%
“…[9] A number of continuous-assay techniques have been developed that employ substrates that release chromogenic, [10][11][12] fluorescent, [13][14][15] and chemiluminescent [16] products upon cleavage of the assay substrate. The common feature of these substrates is a severe modification of their leaving groups compared to DAG (the natural substrate).…”
mentioning
confidence: 99%